Serum alpha-fetoprotein levels in neonatal cholestasis - Demir, Hülya; Hızal, Gülin; Uslu Kızılkan, Nuray; Gürakan, Figen; Talim, Beril; Coşkun, Turgay; Kale, Gülsev; Yüce, Aysel (The Turkish Journal of Pediatrics, 2013)
Alpha-fetoprotein (AFP) is used as a tumor marker for hepatocellular carcinoma, hepatoblastoma and germ cell tumors. It may also be elevated in infants with some hepatobiliary disorders. The mechanism of AFP elevation in neonatal cholestasis is not known. We retrospectively evaluated serum AFP levels in 53 infants with neonatal cholestasis. Thirty patients (56.6%) had elevated AFP, and the ratio of patients with elevated AFP was significantly high in both the metabolic diseases and idiopathic neonatal hepatitis groups (p=0.021). Serum aspartate aminotransferase (AST) levels increased significantly in patients with elevated AFP (p=0.004). Steatosis was the distinctive histopathological finding of the patients with high AFP. The patients with steatosis had significantly higher standard deviation (SD) score of AFP than the patients without steatosis (p=0.001). We have shown AFP elevation in neonatal cholestasis due to metabolic disorders and idiopathic neonatal hepatitis and its association with steatosis and AST elevation.